What Difference Does Good Monitoring and Evaluation Make to World Bank Project Performance? - Raimondo, Estelle (World Bank, Washington, DC, 2016)
For more than 20 years, the development community has claimed that monitoring and evaluation helps projects achieve their objectives. This study uses data from 1,300 World Bank projects evaluated between 2008 and 2014 to investigate this suggested link between the quality of monitoring and evaluation and project performance. The propensity score matching results indicate that the quality of monitoring and evaluation is significantly and positively associated with project outcome as institutionally measured at the World Bank. This positive relationship holds when controlling for project manager identity, and is robust to various specification choices. Through a systematic text analysis of the narrative produced by the Independent Evaluation Group to justify its monitoring and evaluation quality rating, the study shows that there are common markers of good quality monitoring and evaluation, such as: clear institutional setup and division of labor around monitoring and evaluation activities; simple monitoring and evaluation framework that is well aligned with clients' existing monitoring and evaluation systems; good integration with operational tasks; and a system that can generate regular and timely reporting, and that is used during and after lending.